144k views
5 votes
Write an equivalent expression for 4.5x(2 - 6)

User Limavolt
by
5.1k points

2 Answers

4 votes


4.5x(2 - 6) \\ \\ 1. \: 4.5x * - 4 \\ 2. \: = - 18x

User Aadam
by
4.9k points
4 votes


\text{Hey there!}


\text{You could solve this equation by distributing}


\text{The Algebraic I formula for distribution is: a(b + c) = ab + ac}


\text{4.5x(2 - 6)}\\\text{4.5x(2) = 9x}\\\text{4.5x(-6)= -27x}


\text{Combine like terms: 9x - 27x = ?}


\text{Solve that}\uparrow\text{you should get the rest of -18x}


\boxed{\boxed{\text{Answer: -18x}}}\checkmark


\text{Good luck on your assignment and enjoy your day!}

~
\frak{LoveYourselfFirst:)}

User Benoitr
by
5.1k points